2008
DOI: 10.1038/nn.2125
|View full text |Cite
|
Sign up to set email alerts
|

Spike timing–dependent long-term depression requires presynaptic NMDA receptors

Abstract: NMDA receptors are necessary for both synaptic potentiation and depression, but the precise location of these receptors has not been established. By loading MK-801 into pre- or postsynaptic neurons during paired recordings of synaptically connected layer 4 and layer 2/3 neurons in mouse barrel cortex, we found that synaptic potentiation requires postsynaptic, but not presynaptic, NMDA receptors, whereas synaptic depression requires presynaptic, but not postsynaptic, NMDA receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
207
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(234 citation statements)
references
References 15 publications
21
207
6
Order By: Relevance
“…The t-LTD is a neural substrate of some forms of learning and memory that depends on the precise timing of a presynaptic input and a postsynaptic action potential (28). t-LTD occurs when a postsynaptic spike is followed by a presynaptic spike and reflects presynaptic changes in neurotransmitter release that specifically rely on activation of presynaptic NMDA receptors (43). To explore the impact of 5-HT 2A receptor stimulation upon t-LTD induction at thalamocortical synapses, we used a protocol consisting of 75 pairings of an action potential at a layer V pyramidal neuron preceding a layer I-generated EPSP.…”
Section: Resultsmentioning
confidence: 99%
“…The t-LTD is a neural substrate of some forms of learning and memory that depends on the precise timing of a presynaptic input and a postsynaptic action potential (28). t-LTD occurs when a postsynaptic spike is followed by a presynaptic spike and reflects presynaptic changes in neurotransmitter release that specifically rely on activation of presynaptic NMDA receptors (43). To explore the impact of 5-HT 2A receptor stimulation upon t-LTD induction at thalamocortical synapses, we used a protocol consisting of 75 pairings of an action potential at a layer V pyramidal neuron preceding a layer I-generated EPSP.…”
Section: Resultsmentioning
confidence: 99%
“…PreNMDARs also mediate diverse forms of LTP and LTD at subsets of synapses, including timing-dependent LTD at cortical synapses and theta-burst stimulation induced corticalstriatal LTP [45,[64][65][66]. PreNMDARs are therefore likely to bias plasticity and circuit modifica-tion.…”
Section: Synapse-type-specific Long-term Plasticitymentioning
confidence: 99%
“…PreNMDARs are therefore likely to bias plasticity and circuit modifica-tion. In early neocortical development, preNMDARs mediate timing-dependent LTD (tLTD) at L4 to L2/3 synapses [48,66], but tLTD at horizontal L2/3 to L2/3 synapses requires postsynaptic NMDARs [67 •• ,68]. These mechanistic differences may underlie the considerably longer tLTD window at L4 to L2/3 synapses [67 •• ] (Figure 3a-c).…”
Section: Synapse-type-specific Long-term Plasticitymentioning
confidence: 99%
“…Plasticity of synapses between excitatory neurons of layer 4 and layer 2/3 in the barrel cortex has been studied for years as a model of spike timing-dependent plasticity, in which the temporal relation between pre-and post-synaptic action potentials controls synaptic plasticity [48][49][50]. Spike timing-dependent long-term depression (t-LTD) was known to require activation of both CB1Rs and pre-synaptic NMDARs, but how both receptor types cooperatively lead to t-LTD was unknown [48,[51][52][53]. A recent study by Thomas Nevian's laboratory has revealed that astrocytes are crucially involved in this form of synaptic plasticity [11].…”
Section: Role Of Astrocytes In the Regulation Of Long-term Synaptic Pmentioning
confidence: 99%